Analysis of Raw Material Inventory in Production Planning and Control at PT. XYZ - Deo Miliarna; Erni Puspanantasari Putri (JRSI (Jurnal Rekayasa Sistem dan Industri), 2025)
This study was conducted to analyze the imbalance between the manufacture and use of raw materials in the plastic sheet production process at PT XYZ.. As a plastic manufacturing company with an injection molding-based production process, production planning and control (PPIC) plays a crucial role in ensuring the availability of appropriate raw materials to ensure optimal production without shortages or excess stock. Raw material usage data from January to August 2025 showed significant fluctuations and discrepancies between the amount of raw materials produced and used, necessitating an evaluation of material planning methods. This study applied several forecasting methods namely Single Exponential Smoothing and Moving Average to determine the most accurate raw material requirement prediction model. The analysis results showed that the 3-Period Moving Average was the best method with the smallest MAD value and was used as the basis for preparing the Master Production Schedule of 4,585 units per period. The Bill of Material calculation demonstrated efficient material conversion, while the estimation of raw material requirements provided a more accurate picture of procurement planning. Overall, the integration of forecasting, MPS and raw material requirement calculations supports increased production efficiency and more measurable and sustainable decision-making.